Rhus verniciflua as a green corrosion inhibitor for mild steel in 1 M H2SO4. Issue 62 (14th June 2016) - Prabakaran, Mayakrishnan; Kim, Seung-Hyun; Hemapriya, Venkatesan; Gopiraman, Mayakrishnan; Kim, Ick Soo; Chung, Ill-Min
Abstract : The methanolic extract of the plant Rhus verniciflua was examined as a corrosion inhibitor for mild steel in 1 M H2 SO4 through weight loss, UV-visible, FT-IR, electrochemical impedance spectroscopy, and potentiodynamic polarization measurements. Abstract : The methanolic extract of the plant Rhus verniciflua was examined as a corrosion inhibitor for mild steel in 1 M H2 SO4 through weight loss measurements, ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, electrochemical impedance spectroscopy, and potentiodynamic polarization measurements. The sample surface morphology was analyzed using scanning electron microscopy/energy-dispersive X-ray spectroscopy. The total phenolic content of the R. verniciflua leaf extract was found to be 158 mg g −1, while the total flavonoid content was 19.65 mg g −1 . Eleven phenolic compounds, three flavonoid compounds, five derivatives of hydroxycinnamic acid, and four hydroxybenzoic acids were identified in the extract. Polarization studies showed that the R. verniciflua plant extract acts as a good mixed-type inhibitor. The inhibition efficiency was found to increase with an increase in the inhibitor concentration. On the other hand, the inhibition efficiency decreased with an increase in the temperature. The adsorption of the plant extract constituents is discussed based on the Langmuir, Temkin, and El-Awady isotherms. Moreover, the adsorption and thermodynamic parameters corresponding to extract adsorption onto mild steel were calculated and are discussed. The results show that the R. verniciflua plant extract can be employed as an effective corrosion inhibitor with good anticorrosion properties for metals in acidic environments.